The identification of gram positive bacteria and their effects on kidney histopathology of Amazon Sailfin Catfish (Pterygoplichthys pardalis) in Lapompakka and Sidenreng Lakes, Wajo. (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2021)
Pterygoplichthys spp or commonly referred as Pleco is originated from Amazon River in South American Continent.  The aim of this study is to isolate and identify the pathogenic gram-positive bacteria in pleco's kidney (Pterygoplichthys pardalis) and to observe the pleco's kidney histopathology colonized by gram-positive pathogenic bacteria in Sidenreng and Lapompakka Lakes. The samples employed in this experiment includes 10 plecos with each 5 samples represented each lake. The isolation and identification of positive gram bacteria were performed through bacterial culture produced from pleco's kidney swab test on blood agar using gram staining followed by biochemical testing with Vitek 2 compact system. From the results, there were 4 gram-positive bacteria successfully isolated, one of them was Enterococcus faecalis which is the suspected pathogen. Specimen preparation for kidney histopathology was carried out by 10% neutral buffered formalin (NBF) fixation, graded ethanol series dehydration, paraffin wax embedding, 4 μm sectioning, Hematoxylin and Eosin Staining and after that, the specimen was observed. Data analysis employed qualitative descriptive method. From the observation, damages such as necrosis, inflammatory cell infiltration, hemorrhage, and hypertrophy were identified from the pleco's kidney. Kidney damages were most probably caused by the infection by gram-positive pathogenic bacteria Enterococcus faecalis.Keywords : Sidenreng Lake, Lapompakka Lake, Kidney, Histopathology, Plecos.